Transformation of operations with fuzzy sets for solving the problems on optimal motion of crewless unmanned vehicles - Trunov, Alexander (Eastern-European Journal of Enterprise Technologies, 2018)
Solution of an optimization problem of the minimum time of motion of the crewless and unmanned aerial vehicle (CUV) was stated and analyzed. A connection was established between projections of the velocity vector as a condition for solving the problem of minimum travel time. It was proposed to construct an algorithm of correcting parameters of the optimal path. It was shown that if a scale of the value «c» is introduced along the path between two transverse derivatives of the velocity vector module in two orthogonal directions and ensure action of forces which will connect the second derivatives of coordinates in these directions with the same scale of «c», then such path will minimize the total travel time. Separation of motions forms the possibility of control based on video images at a condition of satisfying restrictions of the magnitude of the «c» scale and imposes restrictions on the work of propellers. It was established that calibration of motions makes it possible to determine the «c» constant. Control actions were formed: forces and moments for a hydrodynamic model of the CUV. It was proposed to represent control actions through the number of revolutions of the propeller axle. The control action through a membership function and maximum and minimum ratings of propeller axle rotation speeds was presented. New qualitative concepts were introduced. They are specified by membership functions: speed of rotation of the propeller axle to the values realizable by the motor, µi(ns/nmax); propeller thrust which will provide accelerated motion of the CUV in accordance with rating, µsx(x*,t); lifting force which provides its excess, µsy(x*); speed of rotation of the propeller axle which provides mechanical power at an economical consumption of electric power. The process of choosing speed of rotation of the propeller axle during spatial motion of the CUV has been simulated taking into account influence of such qualitative factors. Simplification of the process of choosing relative speeds of the propeller axles during the period of CUV control has been demonstrated. Based on numerical examples, independence and stability of the calculated value of the function of the intersection belonging and the selected relative propeller axle rotation speeds from the choice of the angles of orientation of the propeller axle were shown.